Indonesiaâ€™s Accounting Fraud Practices: A Literature Study - Rizka Indah Permata Sari Selian; Zalfa Shafira Qatrunnada (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to review a number of theoretical frameworks regarding the reasons why someone commits fraud by involving the fraud triangle theory, the fraud diamond theory, the fraud pentagon theory, and the fraud hexagon theory. This research is a qualitative research with a literature study approach. The data used in this study is secondary data derived from articles with the topic of â€œfraudâ€ in Indonesia for the 2015-2022 research year period. The results of this study indicate that the factors of pressure, opportunity and rationalization have an important role in encouraging someone to commit fraud. Meanwhile, the factors of capability, arrogance, and collusion have not been proven to play a role in encouraging someone to commit fraud. This study is expected to contribute to the accounting literature and can be used in the public sector and organizations. The practical implication of this study is that the public sector and organizations will have a better understanding of the root causes of rampant fraud.